The poles and minima of radiated acoustic power from plate vibration. (February 2018) - Xia, Maolong; Li, Sheng
Abstract: The poles and minima of radiated acoustic power of vibrating plate are discussed and a novel formulation for obtaining the poles and minima is presented. The poles of radiated acoustic power are coincident with the poles of vibration response, the minima of radiated acoustic power can be obtained with knowledge of the location of exciting force, modal radiation efficiencies, poles and modal shapes of structure. An example of a simply supported plate is also presented to illustrate the formulation and provides the comparison between the minima of radiated acoustic power and the corresponding antiresonances. In addition, some applications of poles and minima of radiated acoustic power are discussed in this study.